PELATIHAN PENGELOLAAN KEUANGAN BAGI UMKM PEREMPUAN PENGRAJIN JAMU DI KABUPATEN BANTUL - Dewanti, Patriani Wahyu (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2020)
This community service activity aims to increase the abilities and skills of Small Medium Enterprise (SME) women in Kiringan, Canden, Jetis, Bantul. Those women produce herbal drink and vend it around the villages. This financial management training was to determine the selling price of their products appropriately and use accounting easily in their business activities so that they can prepare simple financial reports.The implementation of Community Service activities was carried out using lecture, tutorial and discussion methods. The activities were divided into fourth times. The first activity was discussing with the headman of the village to decide what training that useful to the citizens, especially for the women entrepreneur who were herbal drink seller. The second activity was to ensure the implementation for community service activity. Furthermore, the team also discussed and finalized the training material. The forward activity was the implementation of community activity. The last activity was a discussion about the financial statement, and the team created the Whatsapp messenger to support this activity